Promoted Ni–Co bimetallic catalysts for glycerol dry reforming : Understanding the physiochemical properties and carbon formation - Nor Shafiqah, Mohd Nasir; Jiao, Yilai; Van Cuong, Nguyen; Sumaiya, Zainal Abidin (Elsevier Ltd, 2024)
Glycerol dry reforming (GDR) is one of the alternatives for syngas production by utilizing glycerol, a by-product of biodiesel. This current work focusing on the effect of Ce, Ru and Pd as promoters on Ni–Co/Al2O3 catalysts. Ultrasonic-assisted impregnation was utilized to synthesize the catalysts and GDR was carried out by varying the reactant partial pressure CO2 to glycerol ranging from 10 to 40 kPa at 1073 K. Characterization studies showed that incorporation of promoter reduced Ni–Co agglomeration and increased metal dispersion on Al2O3 support. This resulted in smaller crystallite size and more consumption of H2 and CO2 based on H2-TPR and CO2-TPD analyses. Irrespective of reactant partial pressure, the catalytic performance was increased with following trend; Ni–Co/Al2O3 < Ce–Ni–Co/Al2O3 < Ru–Ni–Co/Al2O3 < Pd–Ni–Co/Al2O3. The best reactant partial pressure (CO2 and glycerol) was achieved at 20 kPa and the effect of competing reactant caused a significant decline in catalytic performance beyond 20 kPa. Oxygen storage capacity, basic nature and redox cycle of promoters assisting in the carbon reduction on catalysts surface. Overall, Pd–Ni–Co/Al2O3 recorded the highest catalytic activity and lowest carbon formation (7.25%) compared to other promoted catalysts credited to their smallest crystallite size (7.12 nm), great metal dispersion (77.4%, 2.95), highest H2 production, CO2 consumption and oxygen storage capacity.